Analysis of the Technical Performance of Clean Water Distribution at the Tirta Melawi Regional Drinking Water Company - Kelana, Yuni Arinata Putri; Nugraheni, Putranty Widha (Sustainable Environmental and Optimizing Industry Journal, 2022)
In the service area of PDAM Tirta Melawi, there are still several complex issues with the public drinking water system in Indonesia that have not yet been fully fixed. The problem that persists today is the lack of general knowledge of the value of utilizing clean water and the accessibility of clean water services. To address the water needs of the people in the Melawi region, a regional company called the Regional Drinking Water Company (PDAM) Tirta Melawi delivers clean water. The distribution pipe's primary responsibility is to provide clean water to every consumer while taking water pressure, amount, and quality into mind. All customers agree that having access to water on demand is a must-have. The water treatment system, compelling enough to generate water with a whole conventional system, reflects PDAM Tirta Melawi's technical capacity to provide clean water to meet the community's clean water needs. The water distribution capacity can satisfy the water needs of 6,012 consumers, which generates an average of 121,533 m3 at the Tanjung Lay hydropower plant and 51,578 m3 at the Serundung hydropower plant. Nanga Pinoh has a 24-hour service time and up to 14 zones, commencing in zones A through N.